Bending of a generalized circular sandwich plate under a concentrated force with consideration of an improved shear deformation theory - Magnucki, K.; Magnucka-Blandzi, E.; Wittenbeck, L. (Archives of Mechanics, 2022)
The paper is devoted to an axisymmetric bending problem of a generalized circular sandwich plate with continuous variation of mechanical properties in the thickness direction of the core. The plate is clamped and carries a concentrated force in its center. The improved shear deformation theory of the normal straight line to the neutral surface is elaborated. The deformation of this normal straight line is graphically presented for the exemplary sandwich structures of the plate. Two differential equation of equilibrium of the plate are obtained based on the principle of stationary potential energy. This system of equations is analytically solved and the maximum deflection of the example plates are derived. Moreover, the deformation of the normal strain line and the maximum deflection of the plate are calculated numerically (FEM). Results of these calculations are compared.